Medical liability and patient law in Germany: main features with particular focus on treatments in the field of interventional radiology. = Arzthaftung und Patientenrechtegesetz in Deutschland: Die Grund-züge unter besonderer Berücksichtigung von Behandlungen auf dem Gebiet der Interventionellen Radiologie. - Sommer, Sebastian A.; Geissler, R.; Stampfl, Ulrike; Wolf, M. B.; Radeleff, Boris; Richter, Götz Martin; Kauczor, Hans-Ulrich; Pereira, P. L.; Sommer, Christof-Matthias (RöFo, 2016)
On February 26th, 2013 the patient law became effective in Germany. Goal of the lawmakers was a most authoritative case law for liability of malpractice and to improve enforcement of the rights of the patients. The following article contains several examples detailing legal situation. By no means should these discourage those persons who treat patients. Rather should they be sensitized to to various aspects of this increasingly important field of law. To identify relevant sources according to judicial standard research was conducted including first- and second selection. Goal was the identification of jurisdiction, literature and other various analyses that all deal with liability of malpractice and patient law within the field of Interventional Radiology - with particular focus on transarterial chemoembolization of the liver and related procedures. In summary, 89 different sources were included and analyzed. The individual who treats a patient is liable for an error in treatment if it causes injury to life, the body or the patient’s health. Independent of the error in treatment the individual providing medical care is liable for mistakes made in the context of obtaining informed consent. Prerequisite is the presence of an error made when obtaining informed consent and its causality for the patient’s consent for the treatment. Without an effective consent the treatment is considered illegal whether it was free of treatment error or not. The new patient law does not cause material change of the German liablity of malpractice law. Key points: On February 26th, 2013 the new patient law came into effect. Materially, there was no fundamental remodeling of the German liability for medical malpractice. Regarding a physician‘s liability for medical malpractice two different elements of an offence come into consideration: for one the liability for malpractice and, in turn, liability for errors made during medical consultation in the process of obtaining informed consent. Forensic practice shows that patients frequently enforce both offences concurrently. Citation Format: Sommer SA, Geissler R, Stampfl U et al. Medical Liability and Patient Law in Germany: Main Features with Particular Focus on Treatments in the Field of Interventional Radiology. Fortschr Röntgenstr 2016; 188: 353 - 358